“Every Crazy Brings its World”: Madness and Society in the work of Lima Barreto (Research, Society and Development, 2020)
This work aims to analyze the representations of madness in the work "Cemitério dos Vivos" and "Diário Íntimo" by the author Lima Barreto, from his memories during the period spent in the hospice. Analyzing the work, we realize that the author builds another image of madness, in which he writes stories of gestures and feelings. In the work, Lima Barreto unveils the domains of the hospice, social and moral space of exclusion, by criticizing the prison system. To do so, he breaks the silence around madness , by making the dark and silent side of the world of madmen visible, we use the concepts of representation, by author Roger Chartier, to interpret aspects related to madness. Therefore, we use theoretical and methodological concepts of autobiographical research to from Branchot's analysis and Albuquerque Júnior, and to examine the connections of the characters with aspects of this author's personal and professional life using the writings of himself, contributed by the author Ângela Gomes, in order to examine the connections of the characters with aspects of this author's personal and professional life. historical construction of madness by highlighting the contribution of Michel Foucault.